DEVELOPMENT OF PHYSICAL QUALITIES OF STUDENTS BY MEANS OF ATHLETICS (Conferencea, 2023)
The method of physical training of students by means of athletics with the use of repeated, interval and competitive methods for the purpose of complex development of physical qualities is proposed and its effectiveness is proved. The influence of experimental methods on the development of various physical qualities of young men is analyzed. A comparative analysis of the test results with the discharge standards of cross-country athletics disciplines was carried out.